1998
DOI: 10.1111/j.1471-0528.1998.tb10177.x
|View full text |Cite
|
Sign up to set email alerts
|

Effective analgesia following perineal injury during childbirth: a placebo controlled trial of prophylactic rectal diclofenac

Abstract: Objective To determine if diclofenac suppositories administered prophylactically produce effective Design A randomised double blind placebo controlled trial. Setting York District Hospital.Population One hundred women sustaining objective perineal injury (second degree tear or episiotomy) during spontaneous vaginal delivery at term.Methods Suppositories were administered at the time of repair and approximately 12 hours later. The suppositories were randomised prior to issue by the pharmacy department and conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Although this might indicate that the problem of pain postpartum is less significant than we believed at the outset of our study, most literature does indicate that many women suffer significant pain after normal vaginal deliveries. 10,12,13 Our choice to allow 1 of 2 opioidcontaining medications to be administered could be questioned, although it probably did not affect our results. We chose to study nulliparous women hav- ing relatively uncomplicated deliveries to have as homogeneous a sample population as possible, but epidural opioid administration may be more effective in multiparous women, those undergoing instrumental delivery, or those with significant perineal injuries.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although this might indicate that the problem of pain postpartum is less significant than we believed at the outset of our study, most literature does indicate that many women suffer significant pain after normal vaginal deliveries. 10,12,13 Our choice to allow 1 of 2 opioidcontaining medications to be administered could be questioned, although it probably did not affect our results. We chose to study nulliparous women hav- ing relatively uncomplicated deliveries to have as homogeneous a sample population as possible, but epidural opioid administration may be more effective in multiparous women, those undergoing instrumental delivery, or those with significant perineal injuries.…”
Section: Discussionmentioning
confidence: 98%
“…The treatment of postpartum pain has not been extensively studied, but the use of topical lidocaine ointment, different methods of suturing, and both oral and rectal nonsteroidal antiinflammatory drugs have been assessed and have not been shown to be particularly effective. [10][11][12][13] There have been only 2 studies of a 2-mg dose of epidural morphine for treatment of postpartum perineal pain. 5,6 We found that epidural morphine given immedi-ately after vaginal delivery decreased the amount of oral pain medication used in the first 24 hours postpartum.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the mean duration of analgesic therapy for perineal pain was 4.8 days in women who had episiotomies, and only one patient (1.32%), required analgesia for perineal pain for eight days. It has been reported that diclofenac rectal suppositories administered at the time of repair of perineal injury including episiotomies, provides effective analgesia that may continue for up to three days postpartum (17). Assessment of the role of diclofenac in minimising post-episiotomy pain is required in this environment.…”
Section: Discussionmentioning
confidence: 99%
“…13 Searles JA et al, observed that no patient had nausea and vomiting in diclofenac suppository group. 22 In our study, 6 patients (20%) in Inj. diclofenac group complaint of pain at the injection site.…”
Section: Postoperative Complicationsmentioning
confidence: 52%